Proceedings of SPE Asia Pacific Oil and Gas Conference and Exhibition 2005
DOI: 10.2523/93329-ms
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Oil Recovery in Malaysia: Making It a Reality

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractA considerable amount of hydrocarbon resource is estimated to remain in the ground even after primary and secondary recoveries in the fields. As of 2003, the estimated oil-in-place from the forty-seven producing fields in Malaysia stand at about 20.1 BSTB, with a cumulative production of 4.9 BSTB and reserves of 2.5 BSTB 1 . This translates to an averaged recovery factor of only 36.8 percent for producing fields in Malaysia. For this reason, the remaining oil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…In Australia, MEOR was applied in the Alton field producing approximately 40% of incremental oil after 1 year of treatment application [155]. In the Asian region, MEOR has also been deployed in China, India and Malaysia [156,157]. Notable MEOR successes with incremental oil productions ranging up to 204% at field trials have been reported in Argentina, US, Romania, India and Russia [158].…”
Section: Meor Field Applicationsmentioning
confidence: 99%
“…In Australia, MEOR was applied in the Alton field producing approximately 40% of incremental oil after 1 year of treatment application [155]. In the Asian region, MEOR has also been deployed in China, India and Malaysia [156,157]. Notable MEOR successes with incremental oil productions ranging up to 204% at field trials have been reported in Argentina, US, Romania, India and Russia [158].…”
Section: Meor Field Applicationsmentioning
confidence: 99%
“…Oil was first discovered in the Miri district of Sarawak in the early 1900s by one of the biggest oil and gas (OG) companies in the world. The oil exploration offshore of Sarawak found success in 1962, followed by the very first oil field discovery offshore of Peninsular Malaysia in 1971 (Hamdan et al, 2005). That oil discovery promoted opportunity and encouraged more companies to invest in the upstream, midstream and downstream oil industries, including Malaysia's proud OG company, Petroliam Nasional Berhad, which was formed in 1974 in accordance with the Petroleum Act of 1974 (Federal Government Gazette, 1974).…”
Section: Introductionmentioning
confidence: 99%